Modal distribution analysis and sum of sinusoids synthesis of kulintang musical signals - Agsaway, Franklin C. (2005)
Recent developments in time-frequency analysis found applications in various fields including music processing. The developments of fester processors and less expensive memory storage have also made software-based synthesis more accessible to musicians. Analysis and synthesis software have already been developed for various musical instruments. Yet, few of these instruments are ethnic or traditional. The advent of ethnomusicology in Asia, particularly the Philippines, sees the need for software-based synthesis of instruments like those in the Kulintang. A Kulintang is an ensemble of musical instruments played traditionally by the peoples of western Mindanao, particularly in Maguindanao and Lanao. A basic ensemble consists of a dabakan, a babandir, a kulintang, one or two agongs and four gandingans. A dabakan is drum made of lizard or goat skin, while the rest are gongs, or set of gongs, made of iron and bronze. Recordings of Kulintang signal obtained in the Pesudo-Anechoic Audio Room of the UP DSP Laboratory were analyzed using time-frequency analysis. Amplitude and frequency parameters of the signals were obtained from the modal time-frequency distribution of the signals. Finally, synthesis of the signals were done using the obtained parameters in a sum of sinusoids synthesis refined with back-extended exponential decay synthesis. Real-time synthesis was implemented using the ADSP-21065L digital signal processor. The synthesized signals were then evaluated using listening tests.